Importancia del pago de arbitrios municipales en estudiantes de la Facultad de Ciencias Económicas y de Negocios Iquitos año 2024 - Padilla Tello, Alexandra (2025)
The objective of the research was to determine the level of importance of municipal tax payments among students of the Facultad de Ciencias Económicas y de Negocios in Iquitos for the year 2024. The type of study used was basic and the design was non-experimental. It provided relevant results, such as the fact that FACEN students consider the importance of the distribution and use of funds collected from municipal taxes to be medium. Therefore, the study concluded that the level of importance of municipal tax payments among students of the Faculty of Economic and Business Sciences in Iquitos for the year 2024 is medium.